Uravnotežena prehrana v času nosečnosti - Prosen, Mirko (Obzornik zdravstvene nege, 2011)
Introduction: Healthy and balanced nutrition is important in every stage of a womanćs life, in particular before and during pregnancy and lactation. During this time the pregnant woman must ensure adequate energy intake to meet her usual needs, the needs of the developing foetus, and later the needs of a newborn baby. Insufficient nutrient intake is proven to affect not only the developing foetus but the health of the child later in life, and the motherćs health as well. Inadequate nutrition of the pregnant woman, which is reflectedin low or high body weight, has also been linked with the progress and outcome of the delivery. Therefore, the aim of the article is to present some of the main nutritional recommendations that pregnant women should consider. Methods: A descriptive research method was used to perform a literature review which was related to nutrition during pregnancy and was published between 2000 and 2010. The literature used was obtained from databases Wiley Online Library, Sage, ScienceDirect in COBIB.SI. Discussion and conclusions: Expectations that pregnant women will be able to follow all recommended nutritional guidelines are unrealistic, but nurses or midwives canplay a decisive role in pregnant womenćs health education and counselling. The best time for a successful change of eating patterns is before the planed conception or at the beginning of pregnancy when women attend the early pregnancy classes, and when personal consultations with a dietician are recommendable. If possible, nutrition education and guidance along with a personal nutrition plan should be provided, taking into consideration womanćs preferences and her health condition.
Keywords: dietetika; food; human pregnancy; nosečnost; prehrana; zdravstvena nega